PENGARUH PEMBELAJARAN ORGANISASI DAN INOVASI ORGANISASI TERHADAP KINERJA ORGANISASI - Said Hamzali (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine organizational learning and organizational innovation on organizational performance at UPT. Syiah Kuala University Libraries. The sample in this study was taken using a data collection method called the Saturated Sampling Technique (census). The number of samples used was 53 respondents. Primary data collection was carried out by distributing questionnaires. The analysis used in testing the hypothesis is using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the WarpPLS version 5.0 program. The results showed that: 1) organizational learning has a positive and significant effect on organizational performance and 2) organizational innovation has a negative and significant effect on organizational performance.